NON // non a la prison pour les objecteurs // Non au durcissement du code penal militaire // pour un service civil // les 1 et 2 juin votez non
Sicherheitspolitik;Verteidigung;Armee;Militärdienst;Militärdienstpflicht Sicherheitspolitik;Verteidigung;Armee;Militärdienst;Militärdienstverweigerung Sicherheitspolitik;Verteidigung;Armee;Zivildienst